The Best Station of Them All : The Savannah Squadron, 1861-1865 - Melton, Maurice (Book collections on Project MUSE., 2012)
The Best Station of Them All is the story of the Confederate navy's Savannah Squadron, its relationship with the people of Savannah, Georgia, and its role in the city's economy.In this well-written and extensively researched narrative, Maurice Melton charts the history of the unit, the sailors (both white and black), the officers, their families, and their activities aboard ship and in port.The Savannah Squadron worked, patrolled, and fought in the rivers and sounds along the Georgia coast. Though they saw little activity at sea, the unit did engage in naval assault, bo.